HHC RSPP Patient Satisfaction and the Impact of Reliability, Assurance,Tangible, Empathy, and Responsiveness - Rami Agustina; Sarah Handayani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to evaluate the simultaneous or partial effects of service quality, which includes reliability, responsiveness, assurance, empathy, and tangible variables, on patient satisfaction in RSPP Home Care. Patients who participated to the Google survey on customer satisfaction composed the study's sample. the amount of samples of 104 respondents who used the non-probability sampling method were able to collect. Descriptive analysis and multiple regression analysis utilizing the SPSS 25 program provided as the study's analysis method. The finding showed that while partial reliability (X1), assurance (X2), tangible (X3), and tangible (X3) had no impact on patient satisfaction for the HHC RSPP, customer satisfaction for the HHC RSPP was affected by empathy (X4) and responsiveness (X5), and patient satisfaction for the HHC RSPP was simultaneously impacted by all of these quality factors (Y)